Hold Back the Dark - Hooper, Kay (New York, NY : Jove, 2019)
"Madness has taken ahold of Prosperity, North Carolina. Residents are killing one another, as if in a dream, and waking up with no memory of the monstrous acts theyve committed--or why. As the death toll climbs, the local sheriffs department is further rocked by a murder carried out by one of their own. Deputy Katie Cole knows that whatever monster is afoot is beyond her scope... The Special Crimes Unit is called in for their specific brand of investigation. It will take all their training, all their experience, and every extra sense they can call on to get to the bottom of things in Prosperity. And as a dark pattern begins to emerge, even the most experienced and hardened SCU agents have to wonder if this is beyond their understanding" --
Keywords: Bishop, Noah -- (Fictitious character) -- Fiction; United States. -- Federal Bureau of Investigation -- Fiction; Murder -- Investigation -- North Carolina; Fiction; Government investigators -- Fiction; North Carolina -- Fiction; Paranormal fiction; Mystery fiction; Suspense fiction; Detective and mystery fiction